REFLEKSI PRAKTIKUM KIMIA ORGANIK CALON PENDIDIK KIMIA MENGGUNAKAN REKAMAN VIDEO - eko yuliyanto; Yosef Wijoyo; Enade Perdana Istyastono; Fitria Fatichatul Hidayah (Pendidikan Kimia Unimus, 2018)
Organic chemistry is one of the courses that must be taken by a pre-service teacher. However, not all students like the subject, on the other hand they have to learn. Practicum of Organic chemistry has been carried out for some time by chemistry education students. Therefore to bridge the gap and problems. It needs to be an improvement to find out the problem. Therefore it is necessary to reflect on organic chemistry practicum using videos. This research was in the form of observation of learning organic chemistry which was participated by 29 semester 3 chemistry education students with acetic acid synthesis material, saponification and synthesis of butyl acetate. Based on the results of the study concluded that 1). It is important to prepare students' skills in using equipment 2). Practical topics getting closer to everyday products, will be more interesting, 3).Preliminary confirmation before practicum is important to ensure student readiness, 4). Reflection is very helpful in reminding lecturers of the results of learning objectives.